Optimasi Rute Distribusi Gas Lpg 3 Kg dengan Integrasi Algoritma K-Means dan Ant Colony Optimization pada Multiple Travelling Salesman Problem - Liwenki Jus'ma Olivia; Bayu Rahayudi; Imam Cholissodin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Multiple Traveling Salesman Problem (TSP) is a development of the Traveling Salesman Problem in which the TSP only has one salesperson, while the M-TSP can have more than one salesperson With more than one sales, the distribution process will be faster and can reduce transportation costs. PT. Tegal Ombo Makmur is one of the companies that carry out distribution activities in which each salesperson will determine the route of the agent's address to be addressed and it is not uncommon to determine the route that is not efficient or not optimal so that it is a waste of time, energy, and costs. To solve the MTSP problem, this research proposes the use of the K-Means method and the Ant Colony Optimization (K-ACO) Algorithm. The K-Means method is used for optimal city division and then the shortest route will be searched using the ACO Algorithm. The best results were obtained with 4 salesmen and 91 points at the time of iteration at K-Means of 400, parameter NcMax or iterations is 3000, the value of is 1, the value of is 0.9,the value of is 0,9, and the value of is 0.04. Then the total distance generated by the system is 207.94 km, while the total route distance from the company is 466.45 km. Multiple Traveling Salesman Problem (TSP) is a development of the Traveling Salesman Problem in which the TSP only has one salesperson, while the M-TSP can have more than one salesperson With more than one sales, the distribution process will be faster and can reduce transportation costs. PT. Tegal Ombo Makmur is one of the companies that carry out distribution activities in which each salesperson will determine the route of the agent's address to be addressed and it is not uncommon to determine the route that is not efficient or not optimal so that it is a waste of time, energy, and costs. To solve the MTSP problem, this research proposes the use of the K-Means method and the Ant Colony Optimization (K-ACO) Algorithm. The K-Means method is used for optimal city division and then the shortest route will be searched using the ACO Algorithm. The best results were obtained with 4 salesmen and 91 points at the time of iteration at K-Means of 400, parameter NcMax or iterations is 3000, the value of is 1, the value of is 0.9,the value of is 0,9, and the value of is 0.04. Then the total distance generated by the system is 207.94 km, while the total route distance from the company is 466.45 km.